Database Management Systems - H.R. Bobobekova; M.Kh. Nurullayeva (Zien Journals, 2022)
A database management system is a software system designed to create a common database on a computer for many applications, to keep it up-to-date, and to ensure that users can use the information in it effectively within the authority given to them. A database is equally necessary to create and maintain a database of an information system.
Keywords: Databases; relational databases; hierarchical models; information retrieval